AICCRA Additional Financing: West Africa Consultation - Zougmoré, Robert B.; Segnon, Alcade C; Moustapha, Belmira (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Leveraging AICCRA regional partners’ events such as the Regional Market of Agricultural Innovations (MITA) led by CORAF, has boosted level of attendance and diversity of stakeholders to the consultation. New activities and key partners to engage with for the additional financing to enable the operationalization of the new AF orientations at regional level were identified. To operationalize the AF new orientation (the use), there is a need to move from capacity building to capacity development and strategic support (moving beyond capacity building to strengthening strategic engagement and support activities) at regional level. Strengthening ties between AICCRA and the major WB funded initiatives in the region such as the Food System Resilience Program (FSRP) are needed to sustaining regional institutional partnerships for effective development outcomes. There is a need to mainstream more gender and social inclusion dimensions (for example, move from sex desegregation to social differentiation and intersectionality). A recommendation was made for strengthening South-South Learning and collaboration among the partners.